Critical Limit of Mercury and Cadmium on Typic Dystrudepts and Typic Hapluderts of Paddy Field - HUSEIN SUGANDA; ANTONIUS KASNO; BAMBANG HENDRO PRASETYO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2006)
Industrial wastes may pollute agricultural land, which is leading to the contamination of agricultural yield by heavy metals. The pollution of Mercury (Hg) and Cadmium (Cd) on paddy field on rice growth is hard to observe, but the contents of Mercury (Hg) and Cadmium (Cd) on hulled-rice exceed the safety level. Therefore Research should be conducted to study the critical limit of Hg and Cd in soils from paddy field. Soil polluted by Hg and Cd should be remediated physically, chemically, or biologically before it is used for agricultural land. The objectives of the study were to know the effect of heavy metal on harvest yields; to find out the relationship between the contents of Mercury and Cadmium in the soil and in rice, and to determine the critical level of Hg and Cd in the soil. The study was preceded at the laboratory for determining maximum adsorption of Mercury and Cadmium by soil, and then at green house using pots containing Typic Dystrudepts and Typic Hapluderts as muchas 7.5 kg of dry soil. Each pot was given treatments of Mercury and Cadmium with the rate of ; 0, 0.1, 0.2, 0.4, and 0.6 of maximum adsorption by soil, afterward stired and incubated for seven days. Each pot was planted with rice IR-64 as indicator plant. This experiment used Randomised Completely Design with three replicates. The research results showed that the increase of Hg content in soil does not decrease unhulled-rice yield, on the contrary the increase of Cd in soil decreases hulled-rice. Coefficient of correlation (r) between Mercury content in soil and in hulled-rice is 0.79 and 0.94 respectively, while for Cadmium is 0.98 and 0.97. The critical limit of Mercury content in Typic Hapluderts and Typic Dystrudepts is 7.1 and 13.6 mg kg-1 respectively, while the critical limit of Cadmium in Typic Hapluderts and Typic Dystrudepts is 3.9 and 6.9 mg kg-1.